Desafios em aprendizagens matemática com ensino remoto durante a pandemia do COVID-19 - COUTINHO, Amanda Aylla Siqueira (2022)
The present work addressed the thematic teaching Mathematics in Remote Teaching During The Covid-19 Pandemic And Its Challenges, with the aim of discuss the challenges of teaching mathematics through remote teaching during the covid-19 pandemic from the point of viwe of teachers. An online questionnaire was used using the Google Forms tool to obtain the answers from teachers who experienced this atypical period. Thus, according to the reports, the greatest difficulties faced revolve around the lack of technological knowledge to teach classes, the lack of adequate structure and accessories to work at home office, in the same way the students who did not have quality internet access to monitor classes and with that they felt more difficulties in learning mathematics.